Current pattern of use and barriers to implementation of eSanjeevani telemedicine services in Kerala, India - Rosh, P. S. Nabil; Lal, S. S.; Lopez, Serin; Mini, G. K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Kerala State in India presents a distinctive context for studying the implementation and impact of telemedicine, owing to its high levels of digital literacy and relatively well-structured public health infrastructure. This study analyses the adoption and utilization patterns of eSanjeevani, the national telemedicine service, examining both beneficiary and provider perspectives within the state of Kerala. Methods: We conducted a survey among 300 eSanjeevani beneficiaries by covering details of socio-demographics, experiences, motivations for use, patterns of use and challenges. The in-depth interview of key informants assessed implementation challenges in both Outpatient Department and Health and Wellness Centre platforms. Univariate and bivariate analyses were performed for quantitative analysis, while qualitative data were thematically analyzed. Results: Majority (75%) of the beneficiaries were satisfied with eSanjeevani services. However, 21.3% were unaware that the service’s continuation. Users appreciated time savings but reported system glitches, slow platform response, connectivity failures and interface difficulties. Younger, employed, college-educated males found the service easier to use. The findings from stakeholder perspectives highlight critical technical, operational and policy challenges affecting the effective implementation of eSanjeevani. Stakeholders recommended integrating eSanjeevani with national health programs, expanding awareness and improved training for healthcare providers, particularly in mental health services. Conclusions: eSanjeevani has strong potential to expand healthcare access in Kerala, but challenges remain for more awareness on continuity of the services. Efforts to enhance digital skills and address healthcare professionals' concerns are key to ensuring equitable and sustained use of the platform.